2018
DOI: 10.1037/tra0000283
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for coping with individual PTSD symptoms: Experiences of African American victims of intimate partner violence.

Abstract: Findings are discussed in the context of the larger literature on coping and PTSD, specifically regarding (a) coping strategies that may be adaptive or maladaptive and (b) directions for future research that attend to experiences of individual PTSD symptoms. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
2
32
0
2
Order By: Relevance
“…), and that these could have impacts on PTSD symptoms as well. Future research should seek to understand which emotion regulation strategies are most important to assess, and most relevant to PTSD (e.g., Sullivan et al, in press). Third, due to power issues, we could not focus exclusively on trauma-related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…), and that these could have impacts on PTSD symptoms as well. Future research should seek to understand which emotion regulation strategies are most important to assess, and most relevant to PTSD (e.g., Sullivan et al, in press). Third, due to power issues, we could not focus exclusively on trauma-related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has amply analyzed the salient aspects of the psychological process underlying the relational dynamics within which violence in intimate relationships takes place [39][40][41][42] and the consequences on the victims continually exposed to violence [43][44][45][46][47][48].…”
Section: Intimate Partner Violence (Ipv): the Violent Relationship Anmentioning
confidence: 99%
“…There’s great utility in assessing and identifying strategies of coping in traumatic situations, and in this case with PTSD symptoms related to HIV. Researchers have found that African American women use various strategies to cope, such as utilizing social support, use of religious or spiritual support, or avoidance in some cases (Sullivan, Weiss, Price, Pugh, & Hansen, 2017).…”
Section: Introductionmentioning
confidence: 99%